The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.31083/j.rcm2401026
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Left Main Coronary Artery; Untangling the Gordian Knot

Abstract: Left Main Coronary Artery (LMCA) disease is considered a standout manifestation of coronary artery disease (CAD), because it is accompanied by the highest mortality. Increased mortality is expected, because LMCA is responsible for supplying up to 80% of total blood flow to the left ventricle in a right-dominant coronary system. Due to the significant progress of biomedical technology, the modern drug-eluting stents have remarkably improved the prognosis of patients with LMCA disease treated invasively. In fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…A plethora of studies have substantiated the clinical significance of IVUS-guided PCI in enhancing short-, mid-, and long-term clinical and angiographic outcomes [32][33][34]. Against this background, Hannan et al observed a progressive escalation in the utilization of IVUS-guided PCI among patients presenting complex vascular lesions, surging from 13.4% in 2014 to 16.5% in 2018 within New York-based healthcare facilities [35]. These observations align with those made by Mentias et al, who reported a discernible uptick in the utilization of IVUS performance in the context of PCI, which rose from 3.0% in 2009 to 6.9% in 2016 within the United States.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies have substantiated the clinical significance of IVUS-guided PCI in enhancing short-, mid-, and long-term clinical and angiographic outcomes [32][33][34]. Against this background, Hannan et al observed a progressive escalation in the utilization of IVUS-guided PCI among patients presenting complex vascular lesions, surging from 13.4% in 2014 to 16.5% in 2018 within New York-based healthcare facilities [35]. These observations align with those made by Mentias et al, who reported a discernible uptick in the utilization of IVUS performance in the context of PCI, which rose from 3.0% in 2009 to 6.9% in 2016 within the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Subanalyses of the existing meta-analyses did not discover any difference between these two time frames’ regimens [ 32 ]. However, stents’ evolution, intravascular imaging progress and interventional techniques’ development will reduce further ischemic complications (MI, stent thrombosis and revascularization) and trials studying 30- with 90-days DAPT will try to resolve this dilemma [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the progress of interventional techniques, invasive imaging, and the development of novel drug-eluted balloons and biodegradable polymer drug-eluting stents could decrease the risk of ischemic events in patients with diabetes. 21,[27][28][29] Whether patients with diabetes having undergone PCI are under higher risk of major bleeding, compared with nondiabetic remains controversial. Although optimal glycemic control may have a cardioprotective role during acute phase of ACS, it was not associated with a reduced incidence of major bleedings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the progress of interventional techniques, invasive imaging, and the development of novel drug-eluted balloons and biodegradable polymer drug-eluting stents could decrease the risk of ischemic events in patients with diabetes. 21,27–29…”
Section: Discussionmentioning
confidence: 99%